Organizaciones vecinales en municipios de Mendoza : Potencialidad para generar prácticas sociales con inteligencia territorial - Molina, Gladys
The idea of Territorial Intelligence emphasizes the participation of different types from actors in the decisions that concern to the local territory. Between the communitarian actors, the ocal organizations are fundamental because they have an existential knowledge of the geographic space who share the neighbors. That knowledge, is focused generally in the deficiencies of the district or of the district and it is constituted in its reason of being, like average for the defense as opposed to the authority of the local government. This so shared in common function is left lamentably to a quite traditional relation like intermediary between municipality and community annotated. A special case constitutes the cooperative calls of rural services or vicinal organizations that are in charge to administer the service of potable water, those that are generally led by people greater or small proprietors of traditional agriculture. A strong territorial identity can be observed that, as opposed to the transformations and modernization of the field, subsists exactly by that feeling of root. In the province of Mendoza, the importance of the ocal organizations was increased during the decade of the' 90 with the decentralization processes, to canalize house policies, some public works and services in the districts. From a perspective of associated management, projects of economic, cultural, environmental development would have to revitalize their function like organizations able to also agglutinate not only demands but that they promote to the local territory from other dimensions. With these motivations and the purpose of proposing strategies to induce practices of ocal work with territorial intelligence, a set of reflections that allow to compare the space distribution and the characteristics of these organizations between 90 years' and the present time, in some departments of the province of Mendoza appears. The most important result is expressed in a tipología of ocal unions, with a cartography that ties feasible territory and social actors to collaborate to generate transformations social, specially in rural areas
Keywords: Vicinal organizations; Vicinal territory; Associated management